2020
DOI: 10.1002/aelm.202000876
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 2D Electron Gas at the Interface of Atomic‐Layer Deposited Al2O3/ZnO Thin Films for a Field‐Effect Transistor

Abstract: The 2D electron gas (2DEG) phenomenon that occurs at the amorphous thin film hetero‐oxide interface attracts great attention since it can avoid the use of a single‐crystal oxide substrate. In this study, the analysis of 2DEG at the interface of amorphous‐Al2O3 (a‐AO)/ZnO is conducted using ZnO as the bottom substrate, where both the oxide films are grown by atomic layer deposition. Having used Al(CH3)3 as the Al‐precursor for the a‐AO film growth on the previously grown ZnO film, its strong reducing power indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 33 publications
(37 reference statements)
5
20
0
Order By: Relevance
“…Improvements in both I on and negative V th issues were reported by the authors’ group by adopting the ZnO thin film as a substitute for TO . The a -AO/ZnO thin film stack on amorphous SiO 2 exhibited a higher μ Hall of 8.4 cm 2 /(V s) and yielded a higher-performance FET with a low subthreshold swing (SS) of ∼0.33 V/dec and a high on/off ratio of ∼9.4 × 10 6 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Improvements in both I on and negative V th issues were reported by the authors’ group by adopting the ZnO thin film as a substitute for TO . The a -AO/ZnO thin film stack on amorphous SiO 2 exhibited a higher μ Hall of 8.4 cm 2 /(V s) and yielded a higher-performance FET with a low subthreshold swing (SS) of ∼0.33 V/dec and a high on/off ratio of ∼9.4 × 10 6 .…”
Section: Introductionmentioning
confidence: 95%
“…Application of 2DEG at the hetero-oxide superlattice, nanocomposite structure, semiconducting, or insulating hetero-oxide interface as FET channels has been extensively studied recently. Early reports on the emergence of the insulating hetero-oxide-based 2DEG between the hetero-epitaxial LaAlO 3 or amorphous-Al 2 O 3 ( a -AO) films on single-crystal SrTiO 3 have rendered such a Si-compatible device application impractical. However, recent works on the fabrication of thin-film transistor (TFT) devices using the 2DEG generated at the a -AO/polycrystalline TiO 2 ( a- AO/TO) , or a -AO/polycrystalline ZnO ( a- AO/ZnO), which were deposited on SiO 2 /Si substrates, paved the way for the 2DEG to be used for Si-compatible FET applications. In these works, all the dielectric films could be deposited with atomic-scale precision using an industry-compatible atomic-layer deposition (ALD) method, which further strengthens the probability of their commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Later work has demonstrated that 2DEGs can be formed at more simple interfaces, between amorphous and single-crystalline oxides [30,31] with the benefit of room temperature preparation. Recently 2DEGs were shown to form even at amorphous/polycrystalline oxide interfaces [17,21,32,33] (Figure 1C). Furthermore, the oxide deposition temperatures were reduced from 650-900 °C to 25-300 °C, and the deposition techniques have been extended from PLD to the more scalable atomic layer deposition (ALD), which is widely used by the microelectronics industry.…”
Section: Introductionmentioning
confidence: 98%
“…These oxide interfaces provided a fertile ground for the discovery and manipulation of extraordinary physics, such as superconductivity [2][3][4][5], magnetism [6,7], magnetoelectric coupling [8,9], Rashba spinorbit coupling [10], persistent photoconductivity [11,12], and integer/fractional quantum Hall effect [13,14]. Over the last decade, leveraging these phenomena towards various devices, such as transistors [15][16][17][18][19], diodes [20], gas sensors [21], spintronic devices [22,23], and memory devices [24][25][26][27][28][29], has drawn considerable attention. In addition to the exotic phenomena listed above, the emergence of a high sheet density of electrons (typically 10 12 ∼10 15 cm −2 ) between two insulators is already attractive for some devices, such as in the role of channels or back electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation